Cutaneous reactions to carbamazepine in children with epilepsy - Zamiri, Asma; Amoiyan, Sepide; Mostafavi-Toroghi, Sina; Babaei-Hatkehlouei, Mahdi; Moaddabi, Amirhossein; Ebrahimzadeh-Hassanabadi, Mehran; Bakhshi, Tahereh (Chronic Diseases Journal, 2019)
BACKGROUND: The main components in controlling and treating seizures are antiepileptic drugs (AEDs). Mostly, the systemic side effects of these drugs are regarded very important; however, these drugs can also cause serious mucocutaneous side effects. Carbamazepine is a drug which is used to treat epilepsy. Side effects of this drug can range from skin rash to toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS). The purpose of this study was to evaluate skin complications of carbamazepine in children with epilepsy. METHODS: This study was performed on 99 children, aged 2 months to 11 years, with the diagnosis of skin complications after taking carbamazepine. Records were examined and their initial profiles including their medical skin conditions and rashes were recorded within the checklist. Data were entered into SPSS software. Measures of central tendency and dispersion were achieved. Finally, the relationship between the drug and the cutaneous reactions of these patients was analyzed using the chi-square test. RESULTS: The most common complications among the patients were maculopapular lesions and skin erythroderma, with the prevalence of 37.4% for each. Other types of skin lesions included papules with 14.1%, macules with 8.1%, and SJS with 3.0%. A significant association (P = 0.02) between the types of the skin lesion and the dose of carbamazepine was observed; the more the dosage was, the more severe skin lesions were. CONCLUSION: The most common cutaneous reactions to carbamazepine were erythroderma and maculopapular rash in the patients. The findings of this study also revealed that the lack of drug compliance was of high importance.